Principal Management Strategy in Improving Graduates Quality at State Senior High School (SMA Negeri 12) Banda Aceh - Akmaluddin Akmaluddin (JOURNAL OF EDUCATION SCIENCE, 2015)
The purpose of this study was to find out how the principal's strategy in leading teachers and employees in the utilization of various educational resources and the effortprincipals In overcoming obstacles to improve the quality of graduates at SMA N 12 Banda Aceh.This research used qualitative approach with descriptive method. The subjects in this study were principals, teachers, employees and the administration. School supervisors and school committees.The technique of collecting the data wereinterview,observation and documentation.The results of this study showed (1) the principal's strategy in improving the quality ofgraduates in SMA N 12 Banda Acehincluding performing the principal's task as EMASLIM, involving teachers in RPS, MGMP development, conduct teacher professional development and curriculum through workshop activities,study seminars and others. (2) In an effort to improve the quality of graduates at SMA N 12 Banda Aceh, the principal had made the use of various resources that exist professionally, strengthening teacher tasks / professionalism, and involving the community in order to successing the 12-year compulsory education program and the improvement of faith and piety to God Almighty. (3) The principal's strategy in overcoming barriers to quality improvement of graduates at SMA N 12 Banda Aceh, such as, by involving the community in school programs through school committees both quality improvement and fund handling, developing and improving teachers' understanding of the curriculum substance.Keywords: Management of principal's strategy and quality of graduates